Mapping BIM Uses for Risk Mitigation in International Construction Projects - Tsenguun Ganbat; Heap-Yih Chong; Pin-Chao Liao (Advances in Civil Engineering)
International construction projects (ICPs) have become more popular in the current wave of globalization. The Building Information Model (BIM) has been adopted in ICPs. However, the utility of the BIM in ICPs for effective risk control remains unclear. This paper maps the relationship between ICP risks and BIM use to improve the adoption and selection of the BIM. The results show that the BIM can effectively facilitate communication management, mitigating risks engendered by language barriers among stakeholders, for instance, design errors. The BIM can also effectively mitigate risks caused by particular and temporal differences during the construction process. This research highlights internal/technical ICP risks that can be effectively mitigated by certain applications of the BIM; however, in contrast, external risks of ICPs cannot be mitigated by the BIM. However, some risks need to be addressed by new BIM functions. For example, regarding legal risks, laws and regulations of various countries can be included in the BIM information integration model to facilitate timely acquisition of legal provisions by project participants. This study complements prior risk-management research, which typically focused on the BIM as an advanced tool by which to manage project risk, such as design errors, quality, and budget. Practically, the contractor and owner can select suitable BIM applications for different project objectives and risks in the pre-project phase.